2011
DOI: 10.1002/bjs.7345
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after elective minimally invasive colectomy for diverticulitis

Abstract: Elective minimally invasive colectomy is feasible for patients with uncomplicated and complicated diverticulitis, with equivalent outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
2
18
1
1
Order By: Relevance
“…Many studies found that severity of disease was a predictor for conversion, 5,21,37,47-50 but others could not demonstrate a significant difference. 22,51,52 Conversion has traditionally been associated with higher morbidity, 6,7,53 but this has been challenged. 5,37 In a multi-center prospective study of laparoscopic management of diverticulitis, Scheidbach et al found that complication and conversion rates were initially higher in complicated disease but improved with surgeon experience.…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies found that severity of disease was a predictor for conversion, 5,21,37,47-50 but others could not demonstrate a significant difference. 22,51,52 Conversion has traditionally been associated with higher morbidity, 6,7,53 but this has been challenged. 5,37 In a multi-center prospective study of laparoscopic management of diverticulitis, Scheidbach et al found that complication and conversion rates were initially higher in complicated disease but improved with surgeon experience.…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
“…[16][17][18][19][20] Other studies have not used a total laparoscopic approach but have performed technically challenging aspects with a resection-facilitated or hand-assisted technique. 4,[21][22][23] While these techniques improve operating times and preserve tactile feedback, their outcomes may not be comparable with a totally laparoscopic technique with intracorporeal suturing, and the inherent benefits of minimally invasive surgery are reduced.…”
mentioning
confidence: 99%
“…Also Pendlimari et al [32], comparing 136 patients underwent laparoscopic surgery for complicated diverticulitis (including also open perforation, fistula, stricture and bleeding) with 225 patients with uncomplicated disease, found no difference in morbidity, mortality, bowel recovery and conversion rate. Differences in overall morbidity (42 vs. 19.9 %; p = 0.002), wound infection (22 vs. 8.2 %; p = 0.007) and length of stay (6.5 vs. 4.8 days; p \ 0.001) were still found between converted and un-converted group, regardless of whether or not complicated.…”
Section: Hinchey I and Ii Acute Diverticulitismentioning
confidence: 97%
“…In einer großen Analyse einer multizentrischen Datenbank mit 6970 Patienten konnten signifikant niedrigere Komplikationen für das laparoskopische Vorgehen gezeigt werden [30]. Im Vergleich zwischen komplizierter (n = 136) und unkomplizierter Divertikulitis (n = 225) fanden Pendlimari et al [31] …”
Section: Technische Aspekte Und Zeitpunkt Der Operationunclassified